2014
DOI: 10.3126/jkmc.v2i3.9962
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices regarding menstruation among school going adolescents of rural Nepal

Abstract: Background: Adolescence is a transition period from childhood to adult life during which pubertal development and sexual maturation take place, thus making physiological development a challenge adolescents have to face. There is a substantial lacuna in the knowledge towards menstruation among adolescent girls. Menstrual hygiene and management is an issue that is insufficiently acknowledged and has not received adequate attention. Objective: This study was done to assess the knowledge and practices regarding me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
102
6
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(139 citation statements)
references
References 7 publications
29
102
6
2
Order By: Relevance
“…However, internet was the main sources of knowledge (81.2%) among urban adolescents, whereas among rural adolescents girl's mother was the main sources of knowledge regarding menstruation. A study done by Sadiq 13,20,26,[28][29][30] The important finding reported in this study is that teachers were not considered neither as a good source of information nor were they preferred to provide education regarding these matters. Most common problem was abdominal pain, followed by pain in leg, headache/Irritation, and Loss of Appetite.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, internet was the main sources of knowledge (81.2%) among urban adolescents, whereas among rural adolescents girl's mother was the main sources of knowledge regarding menstruation. A study done by Sadiq 13,20,26,[28][29][30] The important finding reported in this study is that teachers were not considered neither as a good source of information nor were they preferred to provide education regarding these matters. Most common problem was abdominal pain, followed by pain in leg, headache/Irritation, and Loss of Appetite.…”
Section: Discussionmentioning
confidence: 92%
“…In studies conducted by Kajal which was similar to our study. 9,12,13 Mean age of menarche among the urban adolescent girls was earlier (11.42±1.66) years and in the rural adolescent girls, it was later (13.12±1.241 years). Studies conducted by Thakre SB, et al and Kamath R, et al in Nagpur and Manipal respectively, documented that the mean age of menarche was 12.85 ± 0.867 years and 13.98 year.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from different parts of India observed the variation of mean age of menarche as Maharashtra (12.99 years),9 Kolkata 14 Average age at menarche in different studies in different time in Nepal was found to be 12 years among the rural adolescent girls in 2007, 15 12.5 years in Sunsari district in 2013, 16 12.94 years in five government schools of Kailali district in 2014. 17 Our study showed that the mean age at menarche among adolescent girls was 12.4 (SD = 1.11).…”
Section: Discussionmentioning
confidence: 99%
“…Menstruation, the periodic vaginal bleeding that occurs with the shedding of the uterine mucosa, is one of the important signs of puberty and occurs one or two years following appearance of secondary sexual characteristics. 1 The first menstruation (menarche) occurs between 11 and 15 years with a mean age of 13 years.…”
Section: Introductionmentioning
confidence: 99%